2015
DOI: 10.1186/s40545-015-0040-8
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ preferences and willingness-to-pay for human papilloma virus vaccines in Thailand

Abstract: ObjectiveTo examine parents’ preferences and willingness-to-pay (WTP) for HPV vaccines.MethodsA discrete choice experiment (DCE) was used. Parents with at least one daughter aged 9–13 years residing in Songkhla province were asked to choose one alternative from each DCE choice set describing HPV vaccines by four attributes, including cervical cancer risk reduction, genital warts risk reduction, common side effects, and cost. Multinomial logit model was used for data analyses.ResultsParents preferred higher ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(60 citation statements)
references
References 23 publications
5
52
1
Order By: Relevance
“…Our study also found that price was an important attribute driving preferences which is in line with previous research [ 9 , 11 , 31 , 50 , 51 ]. Recommended but non-publicly funded vaccines were more likely to be refused by parents due to the price [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study also found that price was an important attribute driving preferences which is in line with previous research [ 9 , 11 , 31 , 50 , 51 ]. Recommended but non-publicly funded vaccines were more likely to be refused by parents due to the price [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…The demographic data indicate a male majority in the sample population, attributed to the fact that the chosen academic institute had female students only from the first to third academic years. As results have elaborated, female students were more knowledgeable of HPV, with 75% of them having high knowledge and none having poor knowledge of HPV, which is in agreement with previously reported findings [1,10-11].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the DCE analysis, those who passed the internal consistency test were included in the main analysis, and the mixed logit estimates are presented in Table 4 [ 30 , 35 ]. The full sample results are comparable with the main analysis and are shown in Table S3 .…”
Section: Resultsmentioning
confidence: 99%